2015
DOI: 10.1002/jcp.25257
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and Epithelial Cell Transition to a Mesenchymal Phenotype Was Delineated by Nestin Expression

Abstract: Endothelial and epithelial cell transition to a mesenchymal phenotype was identified as cellular paradigms implicated in the appearance of fibroblasts and development of reactive fibrosis in interstitial lung disease. The intermediate filament protein nestin was highly expressed in fibrotic tissue, detected in fibroblasts and participated in proliferation and migration. The present study tested the hypothesis that the transition of endothelial and epithelial cells to a mesenchymal phenotype was delineated by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
(89 reference statements)
2
18
0
Order By: Relevance
“…However, hypertrophy alone was not sufficient to induce nestin expression in neonatal and adult cardiomyocytes. [11,23] However, concentric remodeling of the heart was associated with ischemic injury and may represent the incipient event promoting in part the subsequent reactive fibrotic response. [25] Thus, the appearance of nestin (+) -cardiomyocytes in the pressure-overloaded hypertrophied rat heart may be secondary to ectopic ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, hypertrophy alone was not sufficient to induce nestin expression in neonatal and adult cardiomyocytes. [11,23] However, concentric remodeling of the heart was associated with ischemic injury and may represent the incipient event promoting in part the subsequent reactive fibrotic response. [25] Thus, the appearance of nestin (+) -cardiomyocytes in the pressure-overloaded hypertrophied rat heart may be secondary to ectopic ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Nonetheless, the latter paradigm was challenged by several recent studies demonstrating that the majority of collagen type I (+) -mesenchymal cells identified in the interstitial and perivascular regions of the fibrotic pressure-overloaded mouse heart and in the fibrotic rat lungs secondary to hypobaric hypoxia lacked smooth muscle α-actin immunoreactivity. [3,11] Work from our lab revealed that the intermediate filament protein nestin was highly expressed in neonatal rat ventricular fibroblasts, significantly downregulated in adult rat ventricular fibroblasts and recapitulated in scar myofibroblasts during the reparative fibrotic response following myocardial infarction. [6] Nestin was also detected in mesenchymal cells identified in the fibrotic lung and kidney and the accumulation of interstitial collagen following injury of the rat and human kidney positively correlated with the density of nestin (+) -interstitial cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations